2010
DOI: 10.1248/bpb.33.1324
|View full text |Cite
|
Sign up to set email alerts
|

Panax notoginseng Saponins Attenuate Atherogenesis Accelerated by Zymosan in Rabbits

Abstract: Panax notoginseng saponins (PNS) are highly valued traditional Chinese medicine. The effects of PNS (120 mg/kg, once daily administrated intragastrically (i.g.)) on atherosclerosis induced by a high-cholesterol diet and chronic inflammation, which was derived through zymosan (10 mg/kg, once every 2 d) administration intraperitoneally, were evaluated in rabbits for 8 weeks. A normal group, a simple high-fat diet group, and a zymosan plus high-cholesterol diet group (Zym) were used as controls. Typical pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…In accordance with our previous findings in rabbit and rat experiments [9,18], satisfactory anti-atherogenic effect of PNS on apoE -/- mice was observed, displaying decreased size of aortic plaques, reduced ratio of intima-to-media, and alleviation of atherosclerotic pathological changes in arteries. Moreover, the quantitative analysis revealed that PNS treatment was associated with a reduction in intralesional SMCs, particularly in the high-dose PNS-treated mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with our previous findings in rabbit and rat experiments [9,18], satisfactory anti-atherogenic effect of PNS on apoE -/- mice was observed, displaying decreased size of aortic plaques, reduced ratio of intima-to-media, and alleviation of atherosclerotic pathological changes in arteries. Moreover, the quantitative analysis revealed that PNS treatment was associated with a reduction in intralesional SMCs, particularly in the high-dose PNS-treated mice.…”
Section: Discussionsupporting
confidence: 92%
“…Various reagents of PNS, such as Panax notoginseng saponins Injection (Xue Sai Tong Injection), freeze-drying powder of Panax Notoginseng Saponins for Injection are applied clinically in China and are well established to reduce morbidity and mortality from coronary artery disease [7,8], meeting the criterion of the Pharmcopoeia of the People's Republic of China 2010. In addition to the lipid-lowering effects associated with PNS, our previous studies on the anti-atherogenic effects of PNS have shown that it is capable of reducing vascular inflammation, modulating endothelial dysfunction, and decreasing the formation of foam cells via pleiotropic mechanisms [9,10,11,12]. However, the potential role of PNS on EPCs during atherogenesis has not been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies we have addressed the role of PNS in the progression of atherosclerosis and to explore the possible relevant molecular mechanisms. The results showed that PNS treatment significantly decreased the mRNA expression levels of MCP-1 and NF-κB/p65 in the aorta wall after 8 weeks of treatment, indicating that PNS attenuates atherogenesis through an anti-inflammatory action [23]. In addition, the observations in lipopolysaccharide (LPS)-stimulated mouse macrophage cells, RAW264.7 cells suggested that PNS have a strong anti-inflammatory property to suppress the expression of the inflammation-associated genes including inducible nitric oxide synthase, cycloxygenase-2, tumor necrosis factor-alpha and interleukin-1beta by inhibiting the NF-κB activation, resulting in its anti-inflammatory effects [24].…”
Section: Discussionmentioning
confidence: 92%
“…Rats in groups III-VI were given intragastric ethanol infusions to induce chronic liver injury. The ethanol dose was increased gradually by using a method of Zhang 15) as follows: 5.0 g/kg/d from 1 to 4 weeks, 7.0 g/kg/d from 5 to 8 weeks, 9.0 g/kg/d from 9 to 12 weeks. Group III served as the ethanol-induced liver injury model.…”
mentioning
confidence: 99%